Economy has reached the atmosphere: the challenge of the framework climate change law for its adaptation as a public policy - Salvador Cárdenas, Gabriela (2019)
Climate change is one of the main issues we face not only as a country but on a global scale, and it has challenged several countries to achieve a shifiting in state policies, forelooking the climate component’s transversality.Therefore, this article aims to argue the importance of a public policy oriented to climate change adaptation and the influence of the Framework Climate Change Law for the enforzability of decision making for the execution of such policy. Thus, since it is a challenge –as a country- to understand the need of adaptation policies, which are diff erent from mitigation policies, towards the insurance of environmental sustainability for future generations. The climate change adaptation requires a transversal normative reformulation that allows the natural resources guardand the coexistence between environment and citizenship.